Carrières et engagement au sein d’un groupe de supporters de foot en Équateur - Guillaume Fleury (Cahiers des Amériques Latines)
This article deals with analysis of commitment and career in Sur Oscura, barra brava of football club from Barcelona (Ecuador). The aim of this article is to highlight sequential and progressive behaviors to become one of the supporters. This analysis gives keys to understand the place occupied by violent know-how. If violence is not a target for itself, it remains extremely present and is part of daily life of supporters. However, this violence cannot be really understood without analyzing together with festive dimension of barristas activities. Mastering both violent and festive activism allows connections between dominant people and barristas, opening a way to develop political relationships that are strongly led by Sur Oscura's leaders. That way, ethnography of Sur Oscura invites in fact to question social dynamics and external policy which feed its proper practices.